2022
DOI: 10.1007/978-3-031-19433-7_33
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Friendly Biomedical Datasets for Equivalence and Subsumption Ontology Matching

Abstract: Ontology Matching (OM) plays an important role in many domains such as bioinformatics and the Semantic Web, and its research is becoming increasingly popular, especially with the application of machine learning (ML) techniques. Although the Ontology Alignment Evaluation Initiative (OAEI) represents an impressive effort for the systematic evaluation of OM systems, it still suffers from several limitations including limited evaluation of subsumption mappings, suboptimal reference mappings, and limited support fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Therefore, in this study, BERT is combined with fuzzy string-matching algorithms in a fully automated way for ontology alignment. In the study [42], the authors utilized the BERTMap system introduced by He et al [40] to perform the alignment of biomedical ontologies and concluded that BERTMap is convenient for real-world applications. In another study by Bajaj et al [43], the authors study the BERT biomedical variants to see whether they outperform the Siamese Network and original BioBERT.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, in this study, BERT is combined with fuzzy string-matching algorithms in a fully automated way for ontology alignment. In the study [42], the authors utilized the BERTMap system introduced by He et al [40] to perform the alignment of biomedical ontologies and concluded that BERTMap is convenient for real-world applications. In another study by Bajaj et al [43], the authors study the BERT biomedical variants to see whether they outperform the Siamese Network and original BioBERT.…”
Section: Related Workmentioning
confidence: 99%
“…Ontology Pruning We randomly sample a portion (10% or 20%) of the entities in the target ontology, remove them and link the parent and child of each removed entity to preserve the hierarchy as in He et al (2022). This forms a new ontology.…”
Section: Datasetsmentioning
confidence: 99%
“…The closest related work is from Wang et al [29]. They apply LLaMa 65B [26], GPT3.5, and GPT4 to the Biomedical Datasets for Equivalence and Subsumption Matching [5]. The candidate generation is done by computing top k neighbors in an embedding space generated out of SapBERT [13] (a pre-trained BERT model designed for the biomedical domain).…”
Section: Large Language Models For Ontology Matchingmentioning
confidence: 99%
“…The high-precision matcher is a simple matcher in MELT that efficiently searches for concepts with the exact same normalized label (or URI fragment if a label is not available). 5 The normalization includes lowercasing, camel case, and deletion of non alpha-numeric characters. If there is only one such candidate for a concept, then it is matched.…”
Section: High-precision Matchermentioning
confidence: 99%